Peculiarities and Trends of Lithuanian Customs Activities Integrating into European Customs Union - Adomavičiūtė, Danutė (Ekonomika, 2002)
The Customs is one of the most important institutions of the Republic of Lithuania, re-established the same year when the State regained its independence. The Lithuanian Customs is an institution of state control which belongs to the operational activity system and exercises special powers, and to which a particularly great responsibility for the economic protection of the state border falls. The Customs simultaneously ascended the higher step of its activities. Most of them are related with the aims and strategic objectives of the institution which has preferred the way towards the modern European Customs Service. Integration into the Customs Union of the EU countries has formed a clear and principled position of the Lithuanian Customs Administration, i.e. to reorganise resolutely and efficiently the Customs structure and its activity, so that favourable conditions for legitimate foreign trade and speedy movement of flows of travellers and goods across the state border would be created. At the same time, efforts are made to introduce high quality control based on modern information technologies and technical means. With a view to making the work of the Lithuanian Customs consistent and concordant, attempts are made to modernise and improve all its areas as evenly as possible. The data and information presented in Ibis publication virtually reflect the most important changes made by the Lithuanian Customs. Complicated problem, of the Customs Service undergoing rapid changes and everyday concerns related with tax collection, data processing, new technologies, control and work management fall on their shoulders.